Efficacy of axitinib in metastatic head and neck cancer with novel radiographic response criteria. Issue 2 (20th October 2020) - Swiecicki, Paul L.; Bellile, Emily L.; Brummel, Collin V.; Brenner, J. Chad; Worden, Francis P.
Abstract : Background: There are limited treatment options for unresectable recurrent or metastatic (R/M) head and neck squamous cell carcinoma (HNSCC). Vascular endothelial growth factor is of significant interest for targeted therapy in R/M HNSCC because of its central role in tumorigenesis and immunosuppression. Axitinib is a potent inhibitor of vascular endothelial growth factor receptor (VEGFR) 1, VEGFR2, VEGFR3, platelet‐derived growth factor receptor, as well as c‐kit and offers such an approach. Methods: This article reports the results of a phase 2 trial evaluating axitinib in R/M HNSCC according to the Choi criteria for radiographic response assessment. The primary endpoint of this trial was 6‐month overall survival. RESULTS: Twenty‐nine patients were enrolled, and 28 were evaluable for a response. Patients were heavily pretreated with 61% having had at least 1 previous systemic treatment in the metastatic setting (range, 0‐5). The median overall survival of 9.8 months and the 6‐month overall survival rate of 70% met the protocol‐defined criteria for clinical efficacy. The best overall response rate was 42%. Correlative analyses demonstrated that PI3K signaling pathway alterations were associated with an increased response to therapy (75% vs 17%). A marked response to therapy was seen in a subgroup of patients who were treated with an immune checkpoint inhibitor after progression on axitinib. Conclusions: Treatment with axitinib is associated with improved survival in patients with heavily pretreated head and neck cancer, and PI3K pathway alterations may serve as a biomarker for response. Further investigation is warranted to evaluate axitinib in biomarker‐selected populations, especially in combination with immune checkpoint inhibitor therapy. Lay Summary: Metastatic head and neck squamous cancer is an incurable disease with limited treatment options and a poor prognosis. This study is the first to demonstrate that the targeted oral drug axitinib improves survival in patients with heavily pretreated metastatic head and neck cancer. Furthermore, patients whose tumors have specific mutations derive the greatest benefit from therapy. The investigation of axitinib alone or in combination with immunotherapy in a genomic biomarker–selected population is warranted. Abstract : This study demonstrates that treatment with axitinib improves survival in patients with heavily pretreated recurrent or metastatic head and neck squamous cell carcinoma, that alternative response criteria enable the identification of patients with atypical radiographic responses, and that patients with PI3K pathway alterations may derive exceptional benefit from therapy. Clinically, this study provides evidence for the evaluation of axitinib alone or in combination with immunotherapy in a genomic biomarker–selected population.